Global burden of drug use disorders by region and country, 1990–2021 - Zhang, Shuyan; Qi, Xiaoying; Wang, Yingying; Fang, Keyuan (Frontiers in Public Health, 2024)
Background: This study used data from the Global Burden of Disease Study (GBD) database to systematically assess the magnitude of drug use disorders (DUD) burden between 1990 and 2021.Methods: This study used GBD data to analyze the trends in ASIR, DALYs and other DUD indicators from 1990 to 2021, and compared them among different regions and countries. The Estimated Annual Percentage Change (EAPC) and its 95% Confidence Interval (CI) were calculated to assess the temporal and geographical disparities. ASIR and DALYs were used to evaluate the burden of DUDs, and socio-demographic index (SDI) was used to measure the socio-economic development level of each country.Results: The global ASIR of DUDs showed a slight downward trend (EAPC= -0.26). The agestandardized DALY rate ( per 100,000) significantly declined from 1990 to 2021 (EAPC= -1.44). Among the regions, the high SDI region exhibited the most substantial increase in ASIR (EAPC= 0.65). On a regional level, the high-income North America region had the highest EAPC for both age-standardized DALYs and ASIR (EAPC= 4.82,1.02, respectively). Nationally, the United States of America reported the largest increase in age-standardized DALY rates and EAPC for ASIR (EAPC of 4.88,1.05, respectively), while South Africa had the most significant decrease in EAPC (EAPC of -3.62, -1.52, respectively). In 2021, the highest ASIR was observed in high-income North America at 520.07; Central Asia had the highest age-standardized DALY rate. Globally, agestandardized DALYs and ASIR for DUDs were generally higher in men than in women, and the burden of DUDs decreased with age.The global burden of DUDs has shown complex and changing trends over the last decades, with large differences in burden between regions and countries. This highlights the need for targeted public health policies and interventions in High income North America region and Eastern Europe.